Myeloid‐derived suppressor cell‐like fibrocytes are increased and associated with preserved lung function in chronic obstructive pulmonary disease. Issue 4 (10th November 2016) - Wright, A. K. A.; Newby, C.; Hartley, R. A.; Mistry, V.; Gupta, S.; Berair, R.; Roach, K. M.; Saunders, R.; Thornton, T.; Shelley, M.; Edwards, K.; Barker, B.; et al.
Abstract: Background: The role of fibrocytes in chronic obstructive pulmonary disease (COPD) is unknown. We sought to enumerate blood and tissue fibrocytes in COPD and determine the association of blood fibrocytes with clinical features of disease. Methods: Utilizing flow cytometry to identify circulating, collagen type 1 + cells, we found two populations: (i) CD45 + CD34 + (fibrocytes) and (ii) CD45 + CD34 − [myeloid‐derived suppressor cell (MDSC)‐like fibrocytes] cells in stable COPD ( n = 41) and control ( n = 29) subjects. Lung resection material from a separate group of subjects with ( n = 11) or without ( n = 11) COPD was collected for tissue fibrocyte detection. We examined circulating fibrocyte populations for correlations with clinical parameters including quantitative computed tomography (qCT) and determined pathways of association between correlated variables using a path analysis model. Results: Blood and tissue fibrocytes were not increased compared to control subjects nor were blood fibrocytes associated with lung function or qCT, but were increased in eosinophilic COPD. Myeloid‐derived suppressor cell‐like fibrocytes were increased in COPD compared to controls [2.3 (1.1–4.9), P = 0.038]. Our path analysis model showed that collagen type 1 intensity for MDSC‐like fibrocytes was positively associated with lung function through associations with air trapping, predominately in the upper lobes. Conclusion: We have demonstrated that two circulating populations of fibrocyte exist in COPD, with distinct clinical associations, but are not prevalent in proximal or small airway tissue. Blood MDSC‐like fibrocytes, however, are increased and associated with preserved lung function through a small airway‐dependent mechanism in COPD.